Hubungan pusat khidmat setempat (OSC) dengan jabatan-jabatan di dalam pihak berkuasa tempatan (kajian kes : Negeri Perak) - Ahmad, Mohamad Sabri (2010)
The Government is intended to see improvements to public service delivery system through the establishment of the OSC. However, local authorities should be prepared to assume this position of trust to ensure the successful implementation of the OSC. During the period from 13 April 2007 until December 2009 a range of issues and problems identified have been completed. In the meantime there are still complaints related to dissatisfaction with the course of OSC, including OSC unit is seen as a separate entity in the local authority, the understanding of the heads of departments in local authorities on the implementation of OSC, OSC confusion about the scope of work by local authorities and thus do not see the OSC as a catalyst for change in public service delivery system improvements, especially in the business of land development. Therefore, the aim of this study was to investigate the implementation of the One Stop Center (OSC) and its relationship with the local authority technical departments. The objective was to identify the network elements between OSC unit and local authority technical departments in the business of land development, review the understanding of the heads of certain departments in local authorities on the implementation of OSC and recommend improvements to the implementation of the OSC in the local authority system. The study was based on data collection, secondary and primary data. Primary data is data taken directly from the parties through interviews and questionnaires. While secondary data is data obtained from books, magazines, journals, papers, newspaper cuttings, articles and reports. Based on this study found that the relationship of technical departments in local authorities with the OSC is not limited to the four existing technical departments listed in the booklet on the implementation of OSC, but there are four other departments also have a direct relationship with the OSC and it should be involved. In addition to the departments relationship with the OSC can be enhanced by improving the implementation of OSC in the local authority system and the organizational structure of a local authority. Overall understanding of the implementation of the OSC has shown improvement. However, implementation of the OSC system improvements should be detailed to the needs of the departments associated with each item on the implementation of OSC in PBT. It is hoped that this study provides guidance to the Ministry of Housing and Local Government and local authorities to improve public service delivery system in the business of land development in each of their local authorities.